2018
DOI: 10.1111/nyas.13647
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral decoding of working memory items inside and outside the focus of attention

Abstract: How we attend to our thoughts affects how we attend to our environment. Holding information in working memory can automatically bias visual attention toward matching information. By observing attentional biases on reaction times to visual search during a memory delay, it is possible to reconstruct the source of that bias using machine learning techniques and thereby behaviorally decode the content of working memory. Can this be done when more than one item is held in working memory? There is some evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 78 publications
1
31
1
Order By: Relevance
“…However, in these previous studies, each display was to be judged separately before succeeding to the next, which may have enabled participants to periodically refocus on the WM information. Our challenging sequential integration task likely precluded such endogenous reorienting and forced the spatial WM information more persistently into unattendance see also 45 . Consistently, concurrent WM maintenance did not impair overall psychometric sensitivity see also 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in these previous studies, each display was to be judged separately before succeeding to the next, which may have enabled participants to periodically refocus on the WM information. Our challenging sequential integration task likely precluded such endogenous reorienting and forced the spatial WM information more persistently into unattendance see also 45 . Consistently, concurrent WM maintenance did not impair overall psychometric sensitivity see also 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, van Moorselaar and colleagues (2014) did not find attentional guidance at memory set sizes above one-and reported that the absence of the effect could not be explained by imprecise working memory representations or differences in an individual's working memory capacity (see also their successful replication: Frătescu et al, 2019). However, when one of the memory items was retro-cued, they found that the cued item guided attention as effectively as when only a single item was maintained (see also Mallett & Lewis-Peacock, 2018). This result led them to conclude that when multiple items are maintained in working memory only one, uniquely prioritized item can guide attention (see also Downing & Dodds, 2004;Houtkamp & Roelfsema, 2006;Peters, Goebel, & Roelfsema, 2009;Olivers et al, 2011).…”
Section: Do Multiple Working Memory Items Guide Attention Simultaneoumentioning
confidence: 98%
“…When an item becomes permanently irrelevant, it neurally deactivates and no longer casts the same shadow on ongoing maintenance or task performance. That is, information that becomes completely irrelevant (and thus a candidate for permanent removal) is no longer neurally detectable with exogenous stimulation as is temporarily irrelevant information, it is no longer behaviorally detectable with attentional biases on visual search tasks, and it imposes less intrusion cost on memory performance as did temporarily removed information …”
Section: The Mechanisms Of Removalmentioning
confidence: 99%